2019
DOI: 10.1093/brain/awz210
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin complex-associated holoprosencephaly

Abstract: Marked by incomplete division of the embryonic forebrain, holoprosencephaly is one of the most common human developmental disorders. Despite decades of phenotype-driven research, 80–90% of aneuploidy-negative holoprosencephaly individuals with a probable genetic aetiology do not have a genetic diagnosis. Here we report holoprosencephaly associated with variants in the two X-linked cohesin complex genes, STAG2 and SMC1A, with loss-of-function variants in 10 individuals and a missense variant in one. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 60 publications
6
49
1
Order By: Relevance
“…We describe in Table S6 SMC1A 2 / 1 G A T S 3 C M S 1 3 6 8 2 6 8 5 5 3 0 4 2 6 3 3 0 1 Table S6). b Genomic region showing the microdeletions including RAD21 with involvement of other morbid genes (Deardorff et al 2012;Maas et al 2015;Pereza et al 2012;Wuyts et al 2002;Yuen et al 2015), variants reported as variant of unknown significance (VUS) that remained with unknown significance subsequent to re-evaluation, and cases for whom the relationship between phenotype and RAD21 variant could not be confirmed (Kruszka et al 2019;Zhang et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We describe in Table S6 SMC1A 2 / 1 G A T S 3 C M S 1 3 6 8 2 6 8 5 5 3 0 4 2 6 3 3 0 1 Table S6). b Genomic region showing the microdeletions including RAD21 with involvement of other morbid genes (Deardorff et al 2012;Maas et al 2015;Pereza et al 2012;Wuyts et al 2002;Yuen et al 2015), variants reported as variant of unknown significance (VUS) that remained with unknown significance subsequent to re-evaluation, and cases for whom the relationship between phenotype and RAD21 variant could not be confirmed (Kruszka et al 2019;Zhang et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 49 cases, 24 are new. Twentyfive were previously published (Ansari et al 2014;Bonora et al 2015;Boyle et al 2017;Deardorff et al 2012;Dorval et al 2019;Gudmundsson et al 2018;Kruszka et al 2019;Lee et al 2014;Martinez et al 2017;McBrien et al 2008;Minor et al 2014;Yuan et al 2019), and for 19 of these clinical data could be updated (Table 1). Patients originated from Australia, Belgium, Canada, Denmark, Germany, Italy, Netherlands, Spain, Sweden, Switzerland, Turkey, United Kingdom and United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic causes of non‐syndromic holoprosencephaly involve mutations in genes involved in the SHH pathway, the most common of which are SSH , SIX3 , and ZIC2 (Kruszka, Martinez, & Muenke, ). Recently, it was also described that mutations in the chromatid cohesion complex may also cause non‐syndromic holoprosencephaly (Kruszka et al, ). These etiologies of holoprosencephaly do not currently explain the holoprosencephaly phenotype in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, and to our knowledge, only one previous case report of HPE patient with SIX3 variant and CHD is documented in the literature (Poelmans et al, ). In a recent study, we showed that in six patients with HPE and loss of function variant in STAG2 , four (67%) had structural heart anomalies, and furthermore, 58% (7/12) of all reported loss of function variants in STAG2 in the medical literature are associated with structural heart defects (Aoi et al, ; Kruszka et al, ). Interestingly, in the present study, none of the 37 individuals with HPE and ZIC2 variants had CHD, contrasting with previous reports of a 9% incidence of CHD in 157 patients with ZIC2 variants (Solomon et al, ) and a 14% incidence of CHD in 53 patients with ZIC2 variants (Mercier et al, ).…”
Section: Discussionmentioning
confidence: 93%